FAKTOR-FAKTOR KEPUTUSAN WISATAWAN DI OBJEK WISATA RIAU FANTASI LABERSA WATERPARK KABUPATEN KAMPAR - Ramla K; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Riau Fantasi Labersa Water Park tourism object, Kampar Regency since decision making factors as the variable. The aim of this research is to determine the factors influenced the decision making of tourist in doing the tour.The method used in this research was descriptive quantitative where accidental sampling used take the sample. The amount of samples were 100 respondents. The data collection technique used in this research was observation, questionnaire, and documentation. Scale Likert was used to get data quantitativelyAccording to Pitana and Gayatri (2005), there are 4 factors influenced the decision making of tourism, such as: tourist characteristics, awareness the benefit of travel, description of the tour and tourist destination superiority.As the result of this research, the tourists in Riau Fantasi tourism object said that they were agreed about the factors of decision making influenced their decision in doing the tour to Riau Fantasi Labersa Water Park tourism object Kampar Regency. Highest average percentage was in the factor of the awareness of the benefits of the tour 80.5%.Keywords : Decision Making Factors, Tourist, Tourism Object